ISOLASI BAKTERI COCCUS GRAM POSITIF DI DALAM SUSU ULTRA HIGH TEMPERATURE (UHT) 6 DAN 3 BULAN MENJELANG KEDALUWARSA (Isolation of Gram-Positive Cocci Bacteria in Ultra High Temperature (UHT) Processed Milk at 6 and 3 Months Prior to Expiration) - Dedy Sahputra; T. Reza Ferasyi; Ismail Ismail; Razali Razali; Sulasmi Sulasmi; Darmawi Darmawi (Universitas Syiah Kuala, 2016)
This research was aimed to isolate the Gram-positive bacteria that contaminated milk processed with ultra high temperature (UHT) at 6 and 3 months before the date expires. A number of 3 different UHT milk products at 6 and 3 months before expire date were used as sample. Milk samples were taken from several supermarket in Banda Aceh. The identification was conducted using Gram staining method. One ml milk sample was transferred into 18 tubes containing nutrient broth (NB) media and incubated at 37 C for 24 hrs. The sample was then culture on 18 petri discs containing manitol salt agar (MSA) and 18 petri discs containing trypticase soy sucrose bacitracin (TYS20B) using streak plate method. After 2 days, bacterial colonies that grow were identified by Gram staining. The results showed that in UHT processed milk at 6 and 3 prior to expiration contaminated with Gram positive cocci bacteria, which comprised of Staphylococcus aureus and Streptococcus mutant. As conclusion, UHT processed milk at 6 and 3 prior to expiration is contaminated by Gram positive cocci bacteria.